Process safety for engineers an introduction (John Wiley & Sons, Ltd., 2022)
"Many engineers do not have the necessary knowledge of process safety to adequately address process safety concerns; this book fills this need by introducing the reader to the elements of risk based process safety as defined by the CCPS and emphasizes the elements most relevant to an early-career engineers and students. The new edition has been updated with more than 70% new content and the order of topics have been rearranged. Each chapter begins with a detailed case study of a Process Safety incident and includes problem sets, what a new engineer might do, and other incidents. Additionally, the volume of content on each of the elements is commensurate with the importance of that element to a new engineer. For example, much more content is given to hazard identification and risk analysis then to process safety management systems. Finally the book provides a detailed content matrix linking to existing CCPS material and tools and includes problem sets and PowerPoint lectures for each chapter"